Maintaining normothermia: Why and how?. Issue 5 (October 2018) - Trevisanuto, Daniele; Testoni, Daniela; de Almeida, Maria Fernanda B.
Abstract: A high incidence of postnatal hypothermia has been reported in high-as well low-resource countries and it remains an independent predictor of neonatal morbidity and mortality, especially in very preterm infants in all settings. The temperature of newly born infants should be maintained between 36.5 and 37.5 °C after birth through admission and stabilization. Interventions to achieve this may include environmental temperature 23–25 °C, use of radiant warmers, exothermic mattresses, woollen or plastic caps, plastic wraps, humidified and heated gases. Skin-to-skin contact has been used, especially in low-resource settings. The combinations of these interventions applied to quality improvement initiatives, including staff training, use of checklists, and continuous feedback with the staff involved in the management of the neonate, are key factors to prevent heat loss from delivery room to admission to the neonatal intensive care unit. The admission temperature should be recorded as a predictor of outcomes as well as a quality indicator.